Peanut skin polyphenols inhibit toxicity induced by advanced glycation end-products in RAW264.7 macrophages - Fernandes, Annayara Celestina Ferreira; Vieira, Natália Carolina [UNESP]; Santana, Ádina Lima de; Gandra, Renata Luana de Pádua; Rubia, Camila; Castro-Gamboa, Ian [UNESP]; Macedo, Juliana Alves; Macedo, Gabriela Alves (Elsevier, 2020)
This is the first work to use a polyphenolic fraction derived from peanut skin to attenuate the toxicity induced by advanced glycation-end products (AGEs) in RAW264.7 macrophages. The RAW264.7 cells were stimulated by AGEs using the bovine serum albumin-fructose (BSA-FRU), bovine serum albumin-methylglyoxal (BSA-MGO) and arginine-methylglyoxal (ARG-MGO) models. The AGEs increased considerably the levels of reactive oxygen species and the gene expression of proinflammatory cytokines interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and nitric oxide. Twenty-eight polyphenols, including catechin, phenolic acids, and resveratrol were annotated in peanut skin extract (PSE) with the use of ultra-performance liquid chromatography coupled to quadrupole time of flight mass spectrometry (UPLC-QTOF/MSE) and to the UNIFI Scientific Information System. The administration of PSE at 100 and 150 μg/mL significantly inhibited oxidative stress, by suppressing the production of reactive oxygen species up to 70% and reducing the production of nitric oxide, IL-6 and TNF-α up to 1.7-, 10- and 107-fold, respectively.
Keywords: Advanced glycation end-products; Inflammation; Methylglyoxal; Peanut skin; Phenolic compounds; RAW264.7 macrophages